Measuring households' willingness to pay for water quality restoration of a natural urban lake in the Philippines - Bueno, Esther Anne (Animo Repository, 2016)
Lakes are among the most vulnerable ecosystems to the impacts of unregulated industrialization in rapidly urbanizing areas. These threatened ecosystems suffer from policies that lack knowledge of the indirect yet significant roles of regulating ecosystem services. This study utilized contingent valuation to estimate the willingness to pay for the water quality restoration of Sampaloc Lake in San Pablo City, Philippines. Results showed that its five lakeshore villages ascribe a WTP of PHP 177.09/household/month (1 USD = 42.45 PHP) or PHP 7,102,017/year for this service, with 71 % of the respondents willing to pay the given bids to improve and/or rehabilitate the lake’s water quality. The probability of a ‘Yes’ response varied significantly (α = 0.05) with the bid price, location, household income, and respondents’ willingness to participate in water quality management programs for Sampaloc Lake. Results of this study confirm the respondents’ positive willingness to pay for the improvement of Sampaloc Lake’s water quality, indicating the initial feasibility of institutionalizing the Environmental Users Fee System (EUFS) for the household residents. This valuation adds a fresh perspective to ongoing decision-making processes for urban lake management in line with the spreading urbanization in a developing country like the Philippines. This study identifies environmental education on social-ecological interactions as an important prerequisite for holistic policy decisions that will guide the city into sustainably managing its natural lake resources. Further assessment of the lake’s other ecosystem services is recommended for a complete understanding of its total economic value.